Desnutrin/ATGL is Regulated by AMPK and is Required for a Brown Adipose Phenotype - Ahmadian, Maryam (2011)
While fatty acids (FAs) released by white adipose tissue (WAT) provide energy for other organs, lipolysis is also critical in brown adipose tissue (BAT), generating FAs for oxidation and UCP-1 activation for thermogenesis. Here, we show that adipose-specific ablation of desnutrin/ATGL in mice converts BAT to a WAT-like tissue. These mice exhibit severely impaired thermogenesis with increased expression of WAT-enriched genes but decreased BAT genes including UCP-1 with lower PPARα binding to its promoter, revealing the requirement of desnutrin-catalyzed lipolysis for maintaining BAT phenotype. We also show that desnutrin is phosphorylated by AMPK at S406, increasing TAG hydrolase activity, and provide evidence for increased lipolysis by AMPK phosphorylation of desnutrin in adipocytes and in vivo. Despite adiposity and impaired BAT function, desnutrin-ASKO mice have improved hepatic insulin sensitivity with lower DAG levels. Overall, desnutrin is phosphorylated/activated by AMPK to increase lipolysis and brings FA oxidation and UCP-1 induction for thermogenesis.